Emodin from Aloe inhibits Swine acute diarrhea syndrome coronavirus in cell culture - Zheng, Shumei; Wang, Xiaowei; Hu, Huiqiong; Xia, Yongbo; Diao, Xiaoyuan; Qiu, Wenjing; Xue, Chunyi; Cao, Yongchang; Xu, Zhichao (Frontiers in Veterinary Science, 2022)
Swine acute diarrhea syndrome coronavirus (SADS-CoV) is an emerging swine enteropathogenic coronavirus that causes severe diarrhea in neonatal piglets, leading to serious economic losses to the pig industries. At present, there are no effective control measures for SADS, making an urgent need to exploit effective antiviral therapies. Here, we confirmed that Aloe extract (Ae) can strongly inhibit SADS-CoV in Vero and IPI-FX cells in vitro. Furthermore, we detected that Emodin from Ae had anti-SADS-CoV activity in cells but did not impair SADS-CoV infectivity directly. The time-of-addition assay showed that Emodin inhibits SADS-CoV infection at the whole stages of the viral replication cycle. Notably, we found that Emodin can significantly reduce virus particles attaching to the cell surface and induce TLR3 (p < 0.001), IFN-λ3 (p < 0.01), and ISG15 (p < 0.01) expressions in IPI-FX cells, indicating that the anti-SADS-CoV activity of Emodin might be due to blocking viral attachment and the activation of TLR3-IFN-λ3-ISG15 signaling axis. These results suggest that Emodin has the potential value for the development of anti-SADS-CoV drugs.